2016
DOI: 10.1007/s00441-016-2410-1
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of pulsatile hormone treatment for assessing hormone-induced gene expression by cultured rat Sertoli cells

Abstract: In response to various hormonal (follicle-stimulating hormone [FSH] and testosterone [T]) and biochemical inputs, testicular Sertoli cells (Sc) produce factors that regulate spermatogenesis. A number of FSH- and T-responsive Sc-specific genes, necessary for spermatogenesis, have been identified to date. However, the hormone-induced in vitro expression pattern of most of these genes is reported to be inconsistent at various time points in primary rat Sc cultures. As a matter of convenience, cultured Sc are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…As expected, in immature Sertoli cells, genes involved in cell growth and proliferation, metabolism, and the MAPK and Wingless-related integration site (Wnt) pathways were upregulated, whereas in mature cells, genes relevant to the differentiated function of Sertoli cells, involved in phagocytosis, cytoskeleton remodeling, glucose metabolism, and insulin signaling, were expressed. In this study, FSH was delivered with testosterone in a pulsatile fashion, expected to amplify the gene responses, as previously described [60]. This observation is very interesting because it suggests that hormone target cells decode a pulsatile signal vs. a monotonous signal in a quantitatively different manner.…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 76%
See 1 more Smart Citation
“…As expected, in immature Sertoli cells, genes involved in cell growth and proliferation, metabolism, and the MAPK and Wingless-related integration site (Wnt) pathways were upregulated, whereas in mature cells, genes relevant to the differentiated function of Sertoli cells, involved in phagocytosis, cytoskeleton remodeling, glucose metabolism, and insulin signaling, were expressed. In this study, FSH was delivered with testosterone in a pulsatile fashion, expected to amplify the gene responses, as previously described [60]. This observation is very interesting because it suggests that hormone target cells decode a pulsatile signal vs. a monotonous signal in a quantitatively different manner.…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 76%
“…For example, the FSHR couples not only to Gα s but also to Gα i , which is involved in the post-natal mitotic response of Sertoli cells to FSH via extracellular-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK)-dependent signaling [59]. These data are supported by recent evidence that FSH limits the expression of Gα s , which fails to downregulate Gα i activity in infant primates [60]. In this line, a dynamic computational model predicted that PKA inhibition does not compromise phosphatidylinositide(3,4,5) trisphosphate (PIP3) production in pre-pubertal rats [61].…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 83%
“…For example, pulsatile LH-releasing hormonal-therapy was found to be effective over constant GnRH in restoring the normal gonadotropin secretion inducing fertility in men with hypogonadotropic eunuchoidism [ 47 ]. We have recently demonstrated that for hormone induced gene expression study, pulsatile treatment of hormones (both FSH and T in combination) to cultured Sc from 18 days-old pre-pubertal rats’ shows better readouts as compare to that of the conventional, constant stimulation with hormones [ 48 ]. Although the establishment of hypothalamo-hypophyseal testicular axis steadily improves with age in rodents, GnRH pulse generator activity initiates during fetal development [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Claudin-11 is known to be regulated hormonally, and its knockout models result in infertility [87]. In rat primary cultures of testicular Sertoli cells, claudin-11 expression was reported to be modulated both by testosterone as well as follicle-stimulating hormone (FSH) [88]. Additionally, in mice models, suppressed levels of gonadotropins affected the localization of claudin-11 in Sertoli cells [25].…”
Section: Hormonal Regulation Of Claudinsmentioning
confidence: 99%